Impact of increased wood pellet demand on biodiversity in the south‐eastern United States. Issue 11 (15th September 2018) - Duden, Anna S.; Rubino, Matthew J.; Tarr, Nathan M.; Verweij, Pita A.; Faaij, Andre P. C.; van der Hilst, Floor
Abstract: Increasing wood pellet exports from the United States are projected to lead to changes in land use and timberland management, including a shift from natural timberland to pine plantations. These projected changes may impact biodiversity. This study aims to quantify potential biodiversity impacts of increased wood pellet demand in the south‐eastern United States in a spatially explicit manner. We determined differences according to an index of potential species richness (for total, threatened and endemic species and four taxonomic groups) between scenarios of high and low demand for wood pellets, while taking into account potential developments in other wood markets and other land uses. Increased demand for wood pellets was projected to cause both positive and negative biodiversity impacts. Negative shifts in total potential species richness were projected for areas in Florida, coastal Virginia and North Carolina, and parts of the Gulf Coast. Positive shifts in total potential species richness were projected in parts of Oklahoma and Arkansas. In some locations, the direction of change differed per taxonomic group, highlighting the importance of analysing different taxonomic groups. Shifts in potential species richness due to increased wood pellet demand were considerably smaller compared to the changes due to other drivers, such as urbanization and increased timber demand. Biodiversity impacts due to wood pellet demand should therefore be considered in the context of other drivers of land‐use change and biodiversity loss. Our results provide information that allows policymakers, industry and NGOs to focus on areas of concern and take appropriate mitigation measures to limit negative biodiversity impacts and promote positive impacts. The spatially explicit approach presented in this study can be applied to different regions and drivers of land‐use change, to show how projected demand for an internationally traded commodity may lead to impacts on land use and biodiversity in the procurement region. Abstract : Increased demand for wood pellets was projected to cause both positive and negative biodiversity impacts. Negative shifts in total potential species richness were projected for areas including parts of Florida and coastal Virginia while positive shifts were projected in parts of Oklahoma and Arkansas. However, shifts in potential species richness due to increased wood pellet demand were considerably smaller compared to the changes due to other drivers, such as urbanization and increased timber demand.